Development of the Circle Equation E-module: Research on the Effectiveness of Learning Mathematics - Santoso, Hajar Ahmad; Istiqomah, Nisa Rachmi (Universitas Negeri Surabaya, 2022)
This study aims to investigate the effectiveness of the circle equation e-module in learning mathematics. The Canva-based e-module development method using the Four-D model is used in this study. The research was carried out by involving students as research subjects and carried out in a formal education environment. Data were collected through pre-test and post-test, as well as practical assessments and student project assignments. The results showed that (1) the use of the Canva-based circle equation e-module with the Four-D model had a positive and significant impact on student learning outcomes. There is a significant increase in students' understanding of the equation of a circle after using the e-module; (2) This learning e-module is categorized as effective based on the classical mastery achieved by students; (3)This research contributes to the development of a more interactive and effective mathematics education through the use of e-module technology; (4) This research can also encourage collaboration between schools and the dissemination of circle equation e-modules to teachers and students.